Robust Face Alignment for Illumination and Pose Invariant Face Recognition - Kahraman, Fatih; Kurt, Binnur; Gökmen, Muhittin (IEEE, 2007)
In this study we developed AAM based on face alignment method which handles illumination and pose variations. The classical AAM fails to model the appearances of the same identity under different illuminations and poses. We solved this problem by inserting histogram fitting into the searching mechanism and inserting synthetically generated poses